2016
DOI: 10.1016/s0415-6412(16)30008-x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture with manual and electrical stimulation for labour pain: a two month follow up of recollection of pain and birth experience

Abstract: Background: In a previous randomised controlled trial we showed that acupuncture with a combination of manual-and electrical stimulation (EA) did not affect the level of pain, as compared with acupuncture with manual stimulation (MA) and standard care (SC), but reduced the need for other forms of pain relief, including epidural analgesia. To dismiss an under-treatment of pain in the trial, we did a long-term follow up on the recollection of labour pain and the birth experience comparing acupuncture with manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Although there are various instruments for evaluating the childbirth experience, there are a relatively greater number of studies into the perception of the childbirth experience with only one or limited questions [47][48][49][50]. The childbirth experience is a complicated mental concept with various dimensions [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various instruments for evaluating the childbirth experience, there are a relatively greater number of studies into the perception of the childbirth experience with only one or limited questions [47][48][49][50]. The childbirth experience is a complicated mental concept with various dimensions [1].…”
Section: Discussionmentioning
confidence: 99%
“…We found one meta-analysis of randomized trials published in the Cochrane database in 2011 and 6 randomized trials published since then [91][92][93][94][95][96][97]. Of the 6 trials, only 4 reported oxytocin use [94][95][96][97].…”
Section: Acupuncture and Acupressurementioning
confidence: 99%